The Mediating Effect of Employee Engagement on the Relationship Between Transformational Leadership and Organizational Performance - Akoi, Shwana; Ismael , Ferman; Naseri, Tina; Othman, Bestoon (JBS Nexus, 2026)
This study investigates the complex relationship between transformative leadership, employee engagement, and organizational performance in the banking industry of the Kurdistan region of Iraq. This study used a quantitative research methodology to examine the mediating effect of employee engagement on the association between transformational leadership behaviors and organizational performance. A sample of 129 employees was utilized to collect data through online surveys. The acquired data was thenanalyzed using regression and mediation approaches. The results emphasize the beneficial impact of transformative leadership on employee engagement, providing support for the existing body of research. Moreover, the research reveals the significance of employee engagement as an intermediary, enhancing the influence of transformational leadership on the performance of the business. The findings of this study highlight the significance of promoting involved workforces and developing leadership approaches that are in line with the distinct cultural and organizational characteristics of the banking sector in Kurdistan.